Antioxidant dietary fibre from grape pomace flour or extract: Does it make any difference on the nutritional and functional value?. (May 2019) - Beres, Carolina; Freitas, Suely Pereira; Godoy, Ronoel Luiz de Oliveira; de Oliveira, Denize Cristine Rodrigues; Deliza, Rosires; Iacomini, Marcello; Mellinger-Silva, Caroline; Cabral, Lourdes Maria Correa
Graphical abstract: Highlights: Grape pomace flour and aqueous extract were chemically and physically compared as food ingredients. The pomace flour was found to be a fibre-rich foodstuff, mainly rich in insoluble fibre. The pomace extract was also a fibre-rich foodstuff, with enhanced antioxidant capacity and rich in soluble fibre. Yogurt supplemented with the pomace extract had a good overall sensory acceptance. Abstract: White wine Pinot noir grape pomace was dried and milled into flour or extracted in hot water and dried. Both ingredients were analysed and compared according to nutritional and biological value. The extract presented higher mineral and soluble fibre content. After a human digestion simulation, phenolic content and antioxidant capacities were also higher in the extract. After a 5 kDa filtration of the digested fractions, the gastric and enteric retentates from the extract showed higher bioactive value, and gallic, vanillic and seringic acids were the main bioaccessible phenolic compounds. As the extract was a more nutritious and functional ingredient compared to the flour, it was incorporated into a yogurt formulation and tested in a sensorial panel. The overall liking score was 6.2 out of 9.0 and 51% of panellists indicated that certainly would buy the product. The results indicated a promising application for the extract as an antioxidant dietary fibre ingredient.